Mini Book and Audiovisual Interventions Significantly Improve Knowledge in Primigravida Women - Isna Maulida Muits; Happy Dwi Aprilina; Yektiningtyastuti Yektiningtyastuti; Jumiati Riskiyani Dwi Nandia (Indonesian Journal of Global Health Research, 2025)
Low rates of exclusive breastfeeding are generally due to limited knowledge about the benefits of breast milk, which is rooted in a lack of access to adequate information. This suggests that comprehensive education is essential to increase primigravida mothers' knowledge about exclusive breastfeeding. For health education to be more effective, communication media that is engaging and easily understood by mothers are needed. Objective to determine the effect of education using mini books and audiovisual media on the knowledge of third-trimester primigravida women regarding exclusive breastfeeding. A quasi-experimental study with a two-group pre-test–post-test design was conducted. A total of 60 third-trimester primigravida women participated: 30 received a mini book intervention (Purwokerto Timur 1 Health Center, total sampling), and 30 received an audiovisual intervention (Sumbang II Health Center, simple random sampling). Instruments included a video, mini book, and questionnaire with validity test results ranging from 0.502 to 0.986, and a reliability value of 0.768. Data were analyzed using Wilcoxon and Mann-Whitney tests. Both groups showed significant improvements in knowledge (mini book: p = 0.001; audiovisual: p = 0.000). However, no significant difference was found between the two groups in pre-test (p = 0.511) or post-test (p = 0.277) scores. Mini book and audiovisual media are equally effective in increasing knowledge about exclusive breastfeeding among third-trimester primigravida women.